Money patrol: learning financial literacy through games / Nur Adriana Syazwina Ramdzan ... [et al.] - Ramdzan, Nur Adriana Syazwina; Haizan, Elly Elyana; Hanif Sapura, Nur Hijriah; Kasmawi, Zariq Nisa Nasuha; Borhan, Halimahton (Universiti Teknologi MARA, Kedah, 2023)
In Malaysia, awareness of financial literacy among children and youth is at a very low level. This is proven based on a survey conducted by the Malaysian Securities Commission (SC), Malaysian youth are generally unable to manage their finances well. Not only that, a study conducted by the Organization for Economic Cooperation and Development (OECD) and Bank Negara Malaysia (BNM) in 2019 found that one in three Malaysians thought they had a low level of financial knowledge. Financial literacy needs to be nurtured from an early age to help youth form the right attitude in managing their own money. Money Patrol is a multi-player financial budgeting themed board game that was innovated to a digital platform where the game application can be found on the AppStore and Playstore. This game has an educational concept because it is specifically designed to increase players' understanding of the importance of skills and knowledge in financial management. The objective of innovation is to further increase the awareness of financial literacy among its users through the "play while learning" concept. This game encourages users' interest in financial literacy while providing an engaging learning opportunity. Interesting text, audio and animation content, making it a fun game for players to play while increasing their understanding of a subject area. People can install this game app for free on their device and play with their family and friends. Money Patrol aims to attract people of all ages from 9 years old and up to play while learning about how to manage finances. In line with SULAM's objectives, this game can help the community by raising awareness about the value of financial literacy.